Health Literacy of Japanese Elderly who Participated in A Long-term Care Prevention Exercise Program by Household Composition - Tomohiro Kubota; Norikazu Iwamoto; Keisuke Taniguchi; Takazumi Ono; Misato Nihei; Koichi Iwai; Sechang Oh (Sapientia Publishing Group, 2024)
OBJECTIVES With the development of services to improve the daily lives of older adults and the use of Internet of Things technology in healthcare in Japan, there is a growing need to address health literacy, especially among older adults living alone. The current study aims to fill this research gap by assessing the current state of health literacy in this population, and potentially providing guidance for future support strategies. METHODS In this study, 22 older female participants in long-term care preventive services were assessed for health literacy, cognitive function, and activities of daily living using the Household Composition and Basic Demographic Information, the Health Literacy Scale, the Japanese version of the Montreal Cognitive Assessment, and the Occupational Self-Assessment-Short Form. RESULTS The household composition was 13 older adults living alone and nine living with others. Older adults living alone had significantly lower functional health literacy than those living with others, which affected their ability to understand and apply health information. Difficulties reading health materials were also prevalent in this group, suggesting that visual impairment or a lack of assistive devices may affect their understanding of health information. Considering these specific needs through tailored strategies is essential for helping older adults to adapt to an increasingly digital society. CONCLUSIONS Understanding the current state of functional health literacy among older adults living alone in the community is essential for developing strategies to improve their well-being, prevent isolation, and enable them to make informed decisions about their health.